The regional implications of just transition in the world's most coal-dependent economy: The case of Mpumalanga, South Africa - Nel, Etienne; Marais, Lochner; Mqotyana, Zolile (Frontiers in Sustainable Cities, 2023)
Introduction South Africa has had an extraordinarily heavy reliance on coal to fuel its economy, and it is one of the highest carbon dioxide emitters per capita globally. Current moves aligned with COP26 and recently announced Western support for a Just Transition Partnership to support decarbonisation in South Africa and replace coal fired power stations with renewables are to be welcomed. That said, the majority of South Africa's coal mines, thermal power stations and the currently important coal export industry are located in Mpumalanga's Coal-Belt, an area which has and will continue to experience significant social and economic trauma as mines close and workers needs to be reskilled. There are currently over 100,000 workers in the coal and related industries in this region. Methods This paper draws on international and South African evidence of the effects and responses to mine closure, regional resilience theory and evolutionary economic geography theory to analyse the implications and prospects for economic renewal as the coal industry winds down. Evidence is sourced form secondary material including government and industry policy statements and media articles, while primary material was sourced from key informant interviews. Results Transitioning this region of South Africa from its virtual mono-economy based on coal presents challenges which this paper highlights. While support from international sources to help make this transition into renewables will be of considerable benefit, significant challenges need to be addressed to ensure that difficulties are overcome, and the risks of the resource curse experienced in many developing countries are minimized. Discussion Processes may need to be put in place to ensure that the ambitious goal of transitioning from coal to renewables can be achieved, finances and management well-targeted, and a sense of security given to outside investors to help fund the transition, but also broader economic diversification. In parallel to ensure the “transition is just” mechanisms also need to be put in place, by the state and the investors, to ensure that those citizens unable to transition are empowered and engaged in their community to stem the risk of the inevitable frustration and social disturbance that exclusion from the economy and living with declining services creates. Whom should be putting these processes into place also needs consideration given that existing organizations are already struggling. Though not an easy task, it is hoped that this paper sheds some light on the various issues and encourages consideration of the ways to address them.